2018
DOI: 10.3390/ijerph15122767
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Neighbourhood Walkability Index for Porto Metropolitan Area. How Strongly Is Walkability Associated with Walking for Transport?

Abstract: The creation of walkable communities constitutes a cost-effective health promotion strategy, as walking is an accessible and free intervention for increasing physical activity and health. In this cross-sectional ecological study, we developed a walkability index for the Porto Metropolitan Area and we validated it by assessing its association with walking for transportation. Neighborhood walkability was measured using a geographic information system and resulted from the weighted sum of residential density, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 26 publications
1
23
0
4
Order By: Relevance
“…There is wide evidence [1,2] to show that when the urban population takes up walking as a daily activity there is a positive impact on health [3,4], transportation [5,6], economy [7], and air quality [8]. Walking can be promoted as a regular activity [9] and as a means of transport [10,11] when specific infrastructure features are available [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…There is wide evidence [1,2] to show that when the urban population takes up walking as a daily activity there is a positive impact on health [3,4], transportation [5,6], economy [7], and air quality [8]. Walking can be promoted as a regular activity [9] and as a means of transport [10,11] when specific infrastructure features are available [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, prior studies on walkability found that adults living in highly walkable neighborhoods walk significantly more than their counterparts in low-walkable neighborhoods [20]. This is primarily true for walking for transport [21], while findings for recreational walking are less clear [22]. Others found no link between residential density and the total amount of walking [23].…”
Section: Introductionmentioning
confidence: 99%
“…Demikian juga dengan kepadatan, keragaman, desain, dan jarak (Zhao et al 2019). Variabel kepadatan populasi atau hunian, keragaman, desain, konektivitas, aksesibilitas, jarak ke sistem transportasi umum dan penggunaan lahan campuran mendorong aktivitas fisik berjalan kaki dan bersepeda (Ribeiro dan Hoffimann 2018;Kang 2018).…”
Section: Pendahuluanunclassified
“…Demikian juga penelitian ini menunjukkan bahwa tingkat keramahan lingkungan perumahan untuk berjalan kaki tidak cukup berpengaruh pada dorongan untuk melakukan aktivitas fisik, baik untuk berjalan kaki, bersepeda maupun berolah raga. Temuan ini berbeda dengan apa yang ditemukan oleh penelitian-penelitian yang mencoba melihat hubungan antara aktivitas fisik dengan lingkungan yang ramah untuk pejalan kaki (lihat Saelens, Sallis, dan Frank 2003;Ribeiro dan Hoffimann 2018;Kang 2017;2018). Penelitian ini menunjukkan bahwa faktor diluar desain lingkungan perumahan lebih berpengaruh terhadap dorongan untuk melakukan aktivitas fisik.…”
Section: Kesimpulanunclassified